2004
DOI: 10.1111/j.0022-0477.2004.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest tree mortality, recruitment and turnover rates: calculation, interpretation and comparison when census intervals vary

Abstract: Summary1 Mathematical proofs show that rate estimates, for example of mortality and recruitment, will decrease with increasing census interval when obtained from censuses of non-homogeneous populations. This census interval effect could be confounding or perhaps even driving conclusions from comparative studies involving such rate estimates. 2 We quantify this artefact for tropical forest trees, develop correction methods and re-assess some previously published conclusions about forest dynamics. 3 Mortality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
148
1
18

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 38 publications
6
148
1
18
Order By: Relevance
“…In order to correct the bias related to the variation in the interval between censuses, we applied a correction factor (Lewis et al 2004), based on the formula λ corr = λ × t 0.08 , where: λ is the rate and t is the interval in years. We also calculated the number of individuals of each diameter class that persisted, died, were recruited and either immigrated or emigrated (Lieberman et al 1985), as proposed by Spiegel (1976).…”
Section: Basal Area (Ab)mentioning
confidence: 99%
“…In order to correct the bias related to the variation in the interval between censuses, we applied a correction factor (Lewis et al 2004), based on the formula λ corr = λ × t 0.08 , where: λ is the rate and t is the interval in years. We also calculated the number of individuals of each diameter class that persisted, died, were recruited and either immigrated or emigrated (Lieberman et al 1985), as proposed by Spiegel (1976).…”
Section: Basal Area (Ab)mentioning
confidence: 99%
“…Results have been contentious since the first studies suggested that tropical forests were not in long-term equilibrium (Phillips & Gentry 1994, Phillips et al 1998, with criticisms focusing on perceived methodological problems (Clark 2002) and statistical ambiguities (Sheil 1995). Although many of the potential statistical and methodological flaws have since been investigated and resolved Chave et al 2008;Lewis et al 2004cLewis et al , 2009Phillips et al 2002aPhillips et al , 2009, the "changing ecology of tropical forests" hypothesis is still hotly debated (Muller-Landau 2009, Wright 2005. This debate arises, in part, because of inherent limitations in the use of forest plots to detect and understand widespread changes in the functioning of tropical forests, particularly the limited number and length of time such plots have been monitored, and constraints on understanding the drivers of trends given the limited monitoring of the tropical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Muitos estudos abordam a dinâmica das florestas tropicais (Lang & Knight 1983;Lieberman et al 1985;Denslow 1987;Swaine et al 1990;Korning & Balslev 1994;Sheil & May 1996;Laurance et al 1998;Holl 1999;DeWalt et al 2003; Lewis et al 2004;Saiter et al 2011). Especificamente no Brasil, florestas semidecíduas, têm sido estudadas com relativa frequência (Oliveira-Filho et al 1997; Nascimento et al 1999;Chagas et al 2001;Guilherme et al 2004;Appolinário et al 2005;Oliveira-Filho et al 2007;Paiva et al 2007;Higuchi et al 2008;Silva & Araujo 2009).…”
Section: Introductionunclassified